Initial introduction of selected promising foreign medicinal species for establishing a collection of essential-oil plants - Khamraeva, Dilovar T.; Rakhimova, Nargiza K.; Nosirov, Sobit; Bussmann, Rainer W. (Ethnobotany Research and Applications, 2026)
Background: The article presents the results of the initial introduction of several promising foreign medicinal plants aimed at establishing a collection of essential-oil species at the Tashkent Botanical Garden. The obtained data can be used to expand the assortment of medicinal and essential-oil plants, as well as to develop specialized collections and implement new crops in agricultural practice. Methods: Phenological observations and biometric measurements (Shulz 1981) were carried out throughout the growing season of essential-oil plants in 2025. Following the traditional methodology of phenological observations (Methodology… 1975), the dates of the following phenological phases were recorded: onset of vegetation, beginning of budding, flowering period, fruit ripening, and end of the growing season. Results: Under the agrocenosis conditions of the Botanical Garden, the introduced species (Agastache scrophulariifolia, Dracocephalum moldavica, Hyssopus ambiguus, Leonurus cardiaca, Monarda citriodora, Nigella damascena, Origanum laevigatum, Salvia deserta, Scutellaria albida subsp. colchica, Scutellaria altissima) reached the flowering and fruiting phases during their first year of vegetation. For Salvia hispanica, flowering was observed in the second half of October; however, due to a sharp temperature drop, flowering and seed formation were interrupted, and viable seeds were not obtained. In Scutellaria albida subsp. colchica, Scutellaria altissima, and Nigella damascena, self-seeding and rapid transition to generative stages were recorded, indicating their successful adaptation to the introduction conditions. Analysis of flowering times showed a shift compared to their natural habitats, with the introduced species being classified into five groups based on the onset of flowering. Conclusion: The introduced species (Hyssopus ambiguus, Origanum laevigatum, Agastache scrophulariifolia, Leonurus cardiaca, Monarda citriodora, Dracocephalum moldavica, Scutellaria albida subsp. colchica, Scutellaria altissima, Salvia deserta, and Nigella damascena) of alien flora successfully completed a full ontogenetic cycle and produced viable seeds during their first year of vegetation under the conditions of the Botanical Garden. Salvia hispanica is characterized by genetically determined short-day flowering without photoperiodic variability and, considering the successful seed formation in the subtropical zone of Uzbekistan, can be recommended for cultivation in the Surkhandarya region. Scutellaria albida subsp. colchica, Scutellaria altissima, and Nigella damascena successfully regenerate through self-seeding and partially proceed to generative development, indicating their good adaptation to the new growth conditions. Keywords: adaptation, creation of collections, essential oil plants, foreign species, introduction, medicinal plants, phenology.